Development of Virtual Reality Endogen Energy (VREE) Media for Physics Learning Mechanical Wave on Class XI - Anisa Kartikasari; Mita Anggaryani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Computer Virtual Reality (VR) is another innovation in the realm of training that is applied to the educational experience. The improvement of VR innovation in the field of training has experienced a few issues. This study creates learning media in view of VR innovation created by MilleaLab. MilleaLab is a phase for making VR media with extra specific components to make a fair impression of reality to help the educating and developing experience. The headway of VR media which is named "Virtual Reality Endogen Energy (VREE)" This is finished through research, production, approval, and testing. The approval cycle was evaluated by 10 validators who are physical science media speakers and physical science instructor, the media has been pronounced substantial and solid. It shows that the media is suitable for teaching. A limited trial was conducted at one of Senior High School in Sidoarjo. The results show that the media categorised as very good. VREE received positive responses from the respondents who are 30 high school students and 10 students of undergraduate program Physics Education. In brief, " VREE " has been successfully developed as an interactive Physics learning medium that can explain mechanical wave material with volcanic eruptions as themes of study. Further research needs development of VR-based learning media on other topics and need to reiterate the answers to filling out questionnaires by students.